Internet-based maintenance treatment for patients with eating disorders - Güleç, Hayriye; Moessner, Markus; Mezei, Agnes; Kohls, Elisabeth; Túry, Ferenc; Bauer, Stephanie (Professional psychology, research and practice, 2011)
The sustainability of treatment effects is a major challenge in clinical practice. As in most other mental disorders, patients with eating disorders frequently experience relapses following treatment termination. This calls for feasible maintenance strategies that can be implemented in clinical routine at reasonable cost and effort for both treatment providers and patients. This article introduces an Internet-based intervention for maintenance support of patients with bulimia nervosa (BN) and related eating disorders not otherwise specified (EDNOS). The program comprises several online components for psychoeducation, self-help, peer support, and professional counseling. In the present pilot study, 22 women had access to the program for 4 months. The intervention proved feasible and well accepted, and participants' satisfaction with the program was high. Adherence to the various program components was overall acceptable. Patterns of utilization support the assumption that patients with eating disorders have heterogeneous needs for support following treatment termination. The study confirms the potential of flexible and individually tailored Internet-based interventions for the optimization of care for these patients. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Gesehen am 19.07.2022